Listeria monocytogenes contamination of Tenebrio molitor larvae rearing substrate: Preliminary evaluations. (October 2019) - Mancini, Simone; Paci, Gisella; Ciardelli, Valentina; Turchi, Barbara; Pedonese, Francesca; Fratini, Filippo
Abstract: Today, edible insects represent a hot topic as an emerging and eco-friendly source of protein. The mealworm ( Tenebrio molitor L .) is among the most employed insects for human consumption and feed purposes. So far Listeria monocytogenes, have never been detected either in products sold on the market or during the rearing process. In this study, the substrate employed for mealworm rearing was deliberately contaminated with L. monocytogenes and the bacterium was enumerated during the rearing period and after technological treatments of the larvae. L. monocytogenes persisted during the rearing period. Washing the larvae did not produce any significant effect, while fasting the larvae for 24 or 48 h reduced the L. monocytogenes load (P < 0.001). Oven cooking eliminated L. monocytogenes cells from the product, reducing the risk associated to this foodborne pathogen to zero. Highlights: Larvae were reared in contaminated substrate and technological treatments were tested. Listeria monocytogenes persisted in the substrate without affecting larvae viability. Listeria monocytogenes amount was affected by larvae fasting and cooking. No effect was shown by the larvae washing treatment.